RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO AYDIN JAYA - Rachmadana, Haris Pecta; Retnawati, Lestari (Melek IT : Information Technology Journal, 2022)
The Aydin Jaya store is a trading business that sells a variety of daily necessities, the goods sold at the Aydin Jaya store are almost the same as those provided by modern minimarkets. A web-based sales information system is designed to help Aydin Jaya Stores produce desktop-based software for processing sales transaction data at Aydin Jaya Stores. The result of this design is the design of a sales information system that is used to manage computerized data. The problem experienced at the Aydin Jaya Store is recording sales and purchases of goods manually which can risk redundancy and loss of data from sales, as well as difficulties in calculating income and profits. Sales system made web-based using the PHP programming language and MySQL database. The software development methodology used in the system is the waterfall method. The result of making this web system is to assist stores in making sales, such as recording item data, stock, and transaction reports.